2009
DOI: 10.1016/j.jconhyd.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Calcite precipitation dominates the electrical signatures of zero valent iron columns under simulated field conditions

Abstract: Calcium carbonate is a secondary mineral precipitate influencing zero valent iron (ZVI) barrier reactivity and hydraulic performance. We conducted column experiments to investigate electrical signatures resulting from concurrent CaCO 3 and iron oxides precipitation under simulated field geochemical conditions. We identified CaCO 3 as a major mineral phase throughout the columns, with magnetite present primarily close to the influent based on XRD analysis. Electrical measurements revealed decreases in conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
2
13
1
Order By: Relevance
“…Experimental studies on sand and metal sulfides have documented an inverse correlation between sulfide grain size and frequency showing a decrease in the frequency of maximum phase shift with increasing particle size (Olhoeft, 1985;Williams et al, 2005;Wong, 1979). This is consistent with other authors (Revil and Glover, 1998;Slater and Glaser, 2003;Wu et al, 2009) who have shown that frequency dependant responses occur as a function of particle size, surface area, and pore size. Thus if the above assumption holds true for the nanoparticles, then we should observe a decrease in the frequency of maximum phase shift with increasing nano particle concentration as the individual nanocrystals aggregate.…”
Section: The Sip Response Vs Nsrsupporting
confidence: 89%
See 1 more Smart Citation
“…Experimental studies on sand and metal sulfides have documented an inverse correlation between sulfide grain size and frequency showing a decrease in the frequency of maximum phase shift with increasing particle size (Olhoeft, 1985;Williams et al, 2005;Wong, 1979). This is consistent with other authors (Revil and Glover, 1998;Slater and Glaser, 2003;Wu et al, 2009) who have shown that frequency dependant responses occur as a function of particle size, surface area, and pore size. Thus if the above assumption holds true for the nanoparticles, then we should observe a decrease in the frequency of maximum phase shift with increasing nano particle concentration as the individual nanocrystals aggregate.…”
Section: The Sip Response Vs Nsrsupporting
confidence: 89%
“…Individual data points are plotted as white dots. The blue color represents 0-100 Ω-m. thereby masking the polarization properties of the samples (e.g., Wu et al, 2009). In fact, in a study by Wu et al (2008;2009) of electrical properties of ZVI the authors documented that precipitation of nonpolarizable and non-conductive calcite coating on the iron particles reduced their interfacial conduction and polarization, and associated electronic conduction properties.…”
Section: The Sip Response Vs Nsrmentioning
confidence: 99%
“…Their formation therefore enhances further formation and reduction of hydrogen ions. Lo et al (2006) and Wu et al (2009) reported that mainly calcium carbonate causes a decrease in ZVI reactivity, while other reports attributed the main passivating effect to chukanovite (Kohn et al, 2005) or chukanovite with aragonite depositions (Jeen et al, 2007). Other investigations revealed siderite (FeCO 3 ) to be the main precipitate (Agrawal et al, 2002;Mackenzie et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in most cases waste iron contains high amounts of Fe 0 which are directly available for the treatment of contaminants without the need of any pretreatment. These waste materials, as a result of the treatment process, are usually covered with a double layer of iron oxides; however, previous studies showed that when placed in acidic solutions, the outer passive oxide layer is removed or converted by autoreduction to a conducting magnetite film [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, strong emphasis has been recently laid on mixing zero-valent iron with sand to reduce material costs [18], prevent loss of reactivity and hydraulic conductivity and in turn avoid reduction of groundwater flow [19,20]. Addition of sand increases accessible porosity and eliminates both pore clogging and development of preferential flow channels by creating connected pores not subject to infilling by corrosion products such as oxides [13,21]. However, several issues related to interfacial reactions of Fe 0 and its corrosion products with silicon substrates during treatment require further elucidation.…”
Section: Introductionmentioning
confidence: 99%